(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Modern civic identity is based on theories that people consciously strive to maximize their own benefit, and each citizen uses his cognitive abilities for selfish purposes. This theory has several assumptions, and not a family, tribe, nation or other social group, but an individual. Citizens always cooperate in close contact with each other, and in their opinion, it is more beneficial for their personal interests to establish relationships or cooperate with other citizens than to act independently, which is important for studying the evolution of modern concepts of the process of formation of civic identity.